Quality of life of cancer patients with pain treated at a teaching hospital in the interior of the state of São Paulo (Research, Society and Development, 2024)
The research sought to evaluate the quality of life of cancer patients with pain. The study had a quantitative, descriptive, analytical approach, which used the analysis of medical records and the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 to collect data, which was completed during a chemotherapy session with those patients who reported pain assessed using the Visual Scale Analog. The data were analyzed according to the instructions in the manual for the instrument used. It was observed that 60.0% of the participants were women and 40.0% men, 54.02% aged between 50 and 69 years old, of which 26.7% reported moderate pain and 30.8% severe pain, thus such as those who lived with a partner, with education up to the 8th grade, retired, employed and with a history of non-smoking and non-drinking. 27.5% of participants were diagnosed with breast cancer, 72.5% diagnosed less than a year ago, 53.3% with metastasis and 60.8% reported some comorbidity. In the functional and global health scale, according to the quality of life instrument used, the average score was above 60 and in the symptom scale below 40. It was concluded that in the functional and global health scale the average score was demonstrated moderate quality of life, even in the presence of symptoms.